CODE MIXING AND CODE-SWITCHING ANALYSIS IN THE NOVEL OF HONEST OF FAULT - Fenti Mariska Yohana; Nurhayati Nurhayati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: The novel “Honest of Fault” is the novel that bring the readers have to know the codeswitching and code mixing in the text of it. The author more often shown the code mixing thatbased on Fasold and Dell in her text. Code switching and code mixing are contained in every sceneand the author likes to be switching the text from other languages, likes Betawi language in novel.This research is descriptive qualitative, that use the method of content analysis which is describingthe data from sources and the novel itself. From the reduction results by classifying code switchingand code mixing, it was found that there was a lot of code mixing in the text of the novel Honest ofFault rather than code switching. Analysis of code switching and code mixing in this novel is oftenfound to be coded because the author deliberately uses foreign phrases that are more familiar andeasier to understand by readers than using their mother tongue or Indonesian.Key Words: code switching, code mixing, novel.